1999
DOI: 10.1177/107319119900600308
|View full text |Cite
|
Sign up to set email alerts
|

The 2-Year Test-Retest Reliability of the Psychopathy Checklist-Revised in Methadone Patients

Abstract: The 2-year test-retest reliability of the Psychopathy Checklist-Revised (PCL-R) was examined in 200 men and 25 women methadone patients. Stability of the PCL-R was generally good whether it was evaluated as a dichotomous or dimensional measure. Utilizing a diagnostic cutoff score of 25 or more the intraclass correlation coefficients (ICCs) were.48 for men and.67 for women. For the Total PCL-R score ICCs were.60 and.65 for men and women, respectively. Factor 1 was more reliably measured in women compared to men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 15 publications
7
45
4
Order By: Relevance
“…Depending on the amount of information available, testretest correlations ranged from .71 to .76 for Factor 1, whereas they ranged from .79 to .80 for Factor 2 and from .85 to .89 for the total score. Subsequently, Rutherford et al (1999) reported ICC values for PCL-R scores in a much larger sample of male methadone patients (n ¼ 200) participating in their longitudinal research. At a two-year follow-up, again involving independent evaluations and new interviews, Factor 1 scores were significantly less reliable (ICC ¼ .43) than were Factor 2 scores (ICC ¼ .60) or total scores (ICC ¼ .60).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the amount of information available, testretest correlations ranged from .71 to .76 for Factor 1, whereas they ranged from .79 to .80 for Factor 2 and from .85 to .89 for the total score. Subsequently, Rutherford et al (1999) reported ICC values for PCL-R scores in a much larger sample of male methadone patients (n ¼ 200) participating in their longitudinal research. At a two-year follow-up, again involving independent evaluations and new interviews, Factor 1 scores were significantly less reliable (ICC ¼ .43) than were Factor 2 scores (ICC ¼ .60) or total scores (ICC ¼ .60).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of rater agreement findings from more than 120 PCL-R studies found that about half provided little or no information concerning whether independent interviews were used for the cases used to check rater agreement (Rufino et al, 2009). In only a handful of studies was it clear that rater agreement statistics were based on cases in which both evaluators conducted an independent interview (see, e.g., Levenson, 2004;Murrie, Boccaccini, Johnson, & Janke, 2008;Rutherford, Cacciola, Alterman, McKay, & Cook, 1999;Tyrer et al, 2005). In several of these studies, ICC values were notably lower than those reported in the PCL-R manual.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The instability factor includes items related to specific antisocial behaviors and activities . The PCL-R total score has the strongest retest reliability and predictive validity in opioid and other substance dependent samples (McDermott et al, 2000;Rutherford, Cacciola, Alterman, McKay, & Cook, 1999). For the present study, subjects were dichotomized into high (25 or greater total score) and low psychopathy groups (less than 25) as described in the Rutherford et al report (1998).…”
Section: Clinical Assessment Measuresmentioning
confidence: 99%
“…PCL-R total scores of 25 or higher were used to operationally define high psychopathy (e.g., Rutherford et al, 1999); number of APD symptoms was dichotomized into low versus high using a median split. Effects of each variable on outcomes were calculated as unadjusted ORs with 95% CIs.…”
Section: Data Analysesmentioning
confidence: 99%